Timing and modality of kidney replacement therapy in children and adolescents - Thumfart, Julia Angelika; Wagner, Steffen; Kirchner, Marietta; Azukaitis, Karolis; Bayazit, Aysun K.; Obrycki, Lukasz; Canpolat, Nur; Bulut, Ipek Kaplan; Duzova, Ali; Anarat, Ali; Bessenay, Lucie; Shroff, Rukshana; et al. (Kidney international. Reports, 2024)
Introduction - The choice and timing of kidney replacement therapy (KRT) is influenced by clinical factors, laboratory features, feasibility issues, family preferences, and clinicians' attitudes. We analyzed the factors associated with KRT modality and timing in a multicenter, multinational prospective pediatric cohort study. - Methods - A total of 695 pediatric patients with chronic kidney disease (CKD) enrolled into the Cardiovascular Comorbidity in Children with CKD (4C) study at age 6 to 17 years with estimated glomerular filtration rate (eGFR) of 10 to 60 ml/min per 1.73 m2 were investigated. Competing risk regression was performed to identify factors associated with initiation of dialysis or preemptive transplantation (Tx), including primary renal diagnosis, demographics, anthropometrics, and laboratory parameters. - Results - During the 8-year observation period, 342 patients (49%) started KRT. Of these, 200 patients started dialysis, whereas 142 patients underwent preemptive Tx. A lower eGFR at enrolment (Hazard ratio [HR]: 0.76 [95% confidence interval: 0.74-0.78]), a steeper eGFR slope (HR: 0.90 [0.85-0.95], and a higher systolic blood pressure SD score (SDS) (HR: 2.07 [1.49-2.87]) increased the likelihood of KRT initiation. Patients with glomerulopathies were more likely to start dialysis than children with congenital anomalies of the kidneys and urinary tracts (CAKUT) (HR: 3.81 [2.52-5.76]). Lower body mass index (BMI) SDS (HR: 0.73 [0.6-0.89]) and lower hemoglobin (HR: 0.8 [0.72-0.9]) were associated with higher likelihood of dialysis. A significant center effect was observed, accounting for 6.8% (dialysis) to 8.7% (preemptive Tx) of explained variation. - Conclusion - The timing and choice of KRT in pediatric patients is influenced by the rate of kidney function loss, the underlying kidney disease, nutritional status, blood pressure, anemia and center-specific factors.
Online verfügbar 12 June 2024, Version des Artikels 3 September 2024
Gesehen am 14.03.2025